2011
DOI: 10.1007/s10802-011-9549-8
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Equation Analysis of Family Accommodation in Pediatric Obsessive-Compulsive Disorder

Abstract: Family accommodation of symptoms is counter to the primary goals of cognitive-behavioral therapy for pediatric obsessive-compulsive disorder (OCD) and can pose an obstacle to positive treatment outcomes. Although increased attention has been given to family accommodation in pediatric OCD, relatively little is known about associated child and parent characteristics, and their mediating/moderating effects. This study examined a structural equation model of parent and child variables related to parent reports of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
86
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 34 publications
14
86
0
2
Order By: Relevance
“…Alternatively, as it may be difficult for parents to only consider tic-related accommodation (resulting in ratings of more global levels of accommodation), this potentially could partially explain the non-significant association between family accommodation and tic severity, as well as the relationship between family accommodation and other symptomology (e.g., anxiety, externalizing problems). Consistent with findings in pediatric OCD [24,26,31], heightened levels of anxiety and depressive symptoms were linked to increased family accommodation. Youths may present with higher anxiety sensitivity, intolerance of distress, and motivation to complete tasks, increasing the amount of support needed from family members.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Alternatively, as it may be difficult for parents to only consider tic-related accommodation (resulting in ratings of more global levels of accommodation), this potentially could partially explain the non-significant association between family accommodation and tic severity, as well as the relationship between family accommodation and other symptomology (e.g., anxiety, externalizing problems). Consistent with findings in pediatric OCD [24,26,31], heightened levels of anxiety and depressive symptoms were linked to increased family accommodation. Youths may present with higher anxiety sensitivity, intolerance of distress, and motivation to complete tasks, increasing the amount of support needed from family members.…”
Section: Discussionsupporting
confidence: 82%
“…Across pediatric OCD and anxiety, accommodation is ubiquitous, occurring to some degree in virtually all families [14,[21][22][23][24][25][26][27]. Direct associations have been reported between family accommodation and obsessive-compulsive or anxiety severity [26][27][28][29][30], functional impairment [26][27][28][29], child externalizing behaviors [20,23,25,26,28,29,31], and family discord [21]. Accommodation in pediatric OCD and anxiety has been inconsistently related to child age with some finding inverse relations [25] and others finding no significant relationship [22][23][24]28].…”
mentioning
confidence: 99%
“…Among individuals with OCD who are typically developing, accommodation is quite common in families of children and adults, with incidence rates up to 100% and 89%, respectively (Albert et al, 2010;Peris et al, 2008;Storch, Geffken, & Merlo, 2007). Family accommodation is directly associated with obsessive-compulsive symptom severity and functional impairment (Caporino et al, 2012;Flessner et al, 2011;Merlo, Lehmkuhl, Geffken, & Storch, 2009;Storch et al, 2007;Storch, Larson, & Muroff, 2010), and mediates the relationship between symptom severity and functional impairment (Bipeta, Yerramilli, Pingali, Karredla, & Ali, 2013;Caporino et al, 2012;Storch et al, 2007). Several studies have found that family accommodation is directly associated with internalizing and externalizing symptoms (Lebowitz, Omer, & Leckman, 2011;McGuire et al, 2013;Storch et al, 2007;Storch, Jones, & Lack, 2012), while parental anxiety has been linked to increased family accommodation (Caporino et al, 2012;Flessner et al, 2011;Peris et al, 2008).…”
mentioning
confidence: 99%
“…Family accommodation is directly associated with obsessive-compulsive symptom severity and functional impairment (Caporino et al, 2012;Flessner et al, 2011;Merlo, Lehmkuhl, Geffken, & Storch, 2009;Storch et al, 2007;Storch, Larson, & Muroff, 2010), and mediates the relationship between symptom severity and functional impairment (Bipeta, Yerramilli, Pingali, Karredla, & Ali, 2013;Caporino et al, 2012;Storch et al, 2007). Several studies have found that family accommodation is directly associated with internalizing and externalizing symptoms (Lebowitz, Omer, & Leckman, 2011;McGuire et al, 2013;Storch et al, 2007;Storch, Jones, & Lack, 2012), while parental anxiety has been linked to increased family accommodation (Caporino et al, 2012;Flessner et al, 2011;Peris et al, 2008). Family accommodation decreases following CBT (Barrett, Healy-Farrell, & March, 2004;Ferrao et al, 2006;Merlo et al, 2009) and lower baseline levels of family accommodation and greater decreases in family accommodation following treatment are associated with better treatment outcomes (Garcia et al, 2010;Merlo et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation